BESEDI RED PRI ŠKRABCU I PRI MARETIĆU (Filološke studije, 2019)
The author compares views of two influential Slovene and Croatian linguists who lived and worked late in the 19th and in early 20th century, Stanislav Škrabec and Tomo Maretić, on the position of clitic cluster in the sentence structure. She presents and analyses their views on two relevant positions for clitic placement, second position (2p) and initial position (IP). Although both linguists believe in a »real popular speech« as a basis for literary language, their results substantially differ.